1988
DOI: 10.1093/bja/60.2.167
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Fontanelle Pressure Responses to Tracheal Intubation in the Awake and Anaesthetized Infant †

Abstract: In order to define the changes in intracranial pressure which occur during tracheal intubation in young infants, a Ladd transducer was used to monitor anterior fontanelle pressure (AFP) non-invasively in awake (group 1, n = 14) and anaesthetized (group 2, n = 10) infants during intubation of the trachea. Heart rate and systolic arterial pressure were also recorded. In quiet, undisturbed infants, AFP (mean +/- SEM) was similar in groups 1 (9.6 +/- 0.5 mm Hg) and 2 (8.7 +/- 0.8 mm Hg); with crying, AFP increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 8 publications
0
43
0
Order By: Relevance
“…[23][24][25] In addition to improving chances for successful intubation, paralytic agents are reported to attenuate adverse physiologic changes experienced during intubation attempts. Increased intracranial pressure, 2,3,26,27 increased systolic blood pressure 28 and longer duration of hypoxemia 10,29 have been reported in awake vs paralyzed neonatal intubations. The longterm consequences of these physiologic changes are not known.…”
Section: Common Practicesmentioning
confidence: 97%
See 1 more Smart Citation
“…[23][24][25] In addition to improving chances for successful intubation, paralytic agents are reported to attenuate adverse physiologic changes experienced during intubation attempts. Increased intracranial pressure, 2,3,26,27 increased systolic blood pressure 28 and longer duration of hypoxemia 10,29 have been reported in awake vs paralyzed neonatal intubations. The longterm consequences of these physiologic changes are not known.…”
Section: Common Practicesmentioning
confidence: 97%
“…Although several studies have shown adverse effects of awake intubations, [1][2][3] premedication with sedatives, analgesics or paralytics before this invasive procedure is not yet routine. 4 Successful intubations after fewer attempts are reported for chemically paralyzed newborns.…”
Section: Introductionmentioning
confidence: 99%
“…These effects include bradycardia, 2,3 fluctuations in blood pressure (BP), [2][3][4][5][6][7][8] hypoxia, 2,3,7,[9][10][11] and increases in intracranial pressure (ICP). 3,4,6,8,12,13 Previous studies have shown that these potentially adverse effects can be attenuated by using pharmacologic agents. Anticholinergic medication can attenuate the decrease in heart rate (HR), 3,[6][7][8]14 potent analgesics or anesthetic agents can attenuate the hypertensive response, 11 and muscle relaxants have been shown to attenuate the increase in ICP.…”
mentioning
confidence: 99%
“…J. 6 The increases in AFP are greater in the awake than in the anaesthetized infants. Several theories have been advanced to account for this including hypoxaemia and the change in systolic blood pressure.…”
Section: En Anesthdsie Ndonatale L'intubation Endotrachdale Est Souvmentioning
confidence: 95%